FINANCIAL LITERACY, DIGITAL LITERACY, AND ENTREPRENEURIAL INTENTION AMONG UNIVERSITY STUDENTS - Mohammad Rusman Ramli; Ahmad Saiful; Wa Ode Nahra Nafiran (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study examines the effect of financial literacy and digital literacy on entrepreneurial intention among students at Universitas Muhammadiyah Buton. The research was motivated by the institutional agenda to strengthen maritime-based entrepreneurship and Islamic character, while many students who have taken entrepreneurship courses still tend to prefer employment before starting a business. A quantitative associative design was used with 80 student respondents from accounting, management, and agribusiness study programs. Data were collected using questionnaires and analyzed through validity and reliability tests, classical assumption tests, multiple linear regression using SPSS, and structural model confirmation using SmartPLS. The findings indicate that digital literacy has a positive and significant effect on entrepreneurial intention, while financial literacy shows a positive but insignificant effect. The model explains a moderate proportion of variance in entrepreneurial intention. These results suggest that students' ability to use digital media, online information, and digital business platforms is more decisive in shaping entrepreneurial intention than general financial knowledge alone. The study contributes to entrepreneurship education by emphasizing the need to integrate digital business competencies with financial literacy training.